Software Engineering Measurement - C. Munson, John (CRC Press, 2009)
* Helps you develop a solid understanding of measuring software * Shows how to apply scientific method to software measurement * Explains what to measure, how to measure, and how to make the measurements meaningful * Develops static and dynamic measurement techniques * Discusses modeling techniques to establish relationships between software attributes that can be measured and those that can not